Distribution of Xylella fastidiosa in citrus rootstocks and transmission of citrus variegated chlorosis between sweet orange plants through natural root grafts - He, C. X. [UNESP]; Li, W. B.; Ayres, A. J.; Hartung, J. S.; Miranda, V. S.; Teixeira, D. C. (Scientific Societies, 2000)
To study translocation of Xylella fastidiosa to citrus rootstocks, budsticks from citrus variegated chlorosis (CVC)-affected cv. Pera sweet orange (Citrus sinenesis (L.) Osb.) were top grafted on 15 citrus rootstocks. Disease symptoms were conspicuous 3 months later on all 15 rootstocks tested. The presence of X. fastidiosa was confirmed by light microscopy, double-antibody sandwich enzyme-linked immunosorbent assays, and polymerase chain reaction in rootlets and main roots of CVC-symptomatic Pera sweet orange in 11 of the 15 rootstocks tested. These results suggest that bacterial translocation from the aerial plant parts to the root system occurs but is not essential for X. fastidiosa to induce symptoms in the aerial parts. Bacterial translocation to the roots was not correlated with CVC leaf-symptom severity in the Pera scion. To determine if CVC disease could be transmitted by natural root grafts, two matched seedlings of each of four sweet orange cultivars (Pera, Natal, Valencia, and Caipira) were transplanted into single pots. One seedling rootstock of each pair was inoculated by top grafting with a CVC-contaminated budstick while the other seedling rootstock was cut but not graft inoculated. Transmission of X. fastidiosa from an inoculated plant to a noninoculated plant sharing the same pot was observed in all four sweet orange cultivars tested. Transmission was confirmed by observation of natural roots grafts between the two plants, presence of X. fastidiosa in the root grafts, and disease development in the uninoculated plants. This is the first report of transmission of CVC disease through natural root grafts.
Keywords: Citrus; Plant-pathogenic bacteria; Xylem; Xylem-inhabiting bacteria; bacterial infection; bacterial translocation; citrus variegated chlorosis; cultivar; disease transmission; enzyme linked immunosorbent assay; graft hybridization; microscopy; orange; pathogenesis; polymerase chain reaction; rootstock; Citrus sinensis; Xylella fastidiosa